Cave insects with sex‐reversed genitalia had their most recent common ancestor in West Gondwana (Psocodea: Prionoglarididae: Speleketorinae). Issue 3 (9th August 2019) - Yoshizawa, Kazunori; Lienhard, Charles; Yao, Izumi; Ferreira, Rodrigo L.
Abstract: The divergence date and ancestral distributional area of the psocid subfamily Speleketorinae, which includes taxa with reversed genitalia (female penis and male vagina of Afrotrogla and Neotrogla, tribe Sensitibillini), were estimated. The most basal divergence of the subfamily (between the North American Speleketor and the tribe Sensitibillini) was estimated to have occurred according to the separation between the North American continent and Gondwana, ca. 175 Ma. The most basal divergence of Sensitibillini (between African Afrotrogla + Sensitibilla and Brazilian Neotrogla ) was estimated to have occurred according to the split of West Gondwana (separation between the African and South American continents), ca. 127 Ma. The biome of the ancestral distributional area of Sensitibillini (inland of West Gondwana) is believed to be arid to semi‐arid, which might strengthen the reversed sexual selection and then facilitate the origin of preadaptive features related to the evolution of a female penis. All extant Sensitibillini species inhabit carbonatic caves, but geological evidence suggested independent shifts of these genera to the carbonatic cave habitat in the Tertiary/Quaternary. Abstract : The barklouse tribe Sensitibillini is especially famous for having female penis in some genera ( Afrotrogla and Neotrogla ). The biogeographical and divergence date analyses showed that the common ancestor of this tribe was distributed in western Gondwana, and the present distributional pattern is formed by the continental vicariance between Africa and South America.